NOVA CONTRIBUIÇÃO AO ESTUDO DO CONTRÔLE DE NEMATÓIDES EM CULTURAS DE BATATA DOCE - Boock, O. J. (REVISTA DE AGRICULTURA, 2016)
NOVA CONTRIBUIÇÃO AO ESTUDO DO CONTRÔLE DE NEMATÓIDES EM CULTURAS DE BATATA DOCE